Hubungan Dukungan Sosial Pasangan dan Resiliensi Akademik pada Mahasiswa Berpacaran - Aldhi Firman Maulana; Retnaningsih Retnaningsih (Jurnal Ilmu Kedokteran dan Kesehatan Indonesia, 2025)
The many pressures and problems in the academic world can have a bad impact on students who experience them. Therefore, students need to have academic resilience. One of the things that can increase academic resilience is partner social support. This study aims to empirically examine the relationship between partner social support and academic resilience in dating students. The research method used in this study is a quantitative method. The sampling technique used is purposive sampling, with the criteria of male and female students and having a partner. The sample in this study amounted to 101 respondents. The data collection technique was carried out using a questionnaire in the form of a google form. The academic resilience scale was compiled based on aspects of academic resilience with an Alpha Cronbach value of 0.868. The couple's social support scale was compiled based on the couple's social support aspects with an Alpha Cronbach value of 0.845. Based on the results of the study, a correlation coefficient value of 0.417 and a significance value of 0.000 (p < 0.05) were obtained. These results show that there is a very significant positive relationship between the social support of the couple and the academic resilience of the dating students.